Pengaruh Daun Jambu Biji terhadap Nyeri Haid (Dysmenorrhea) pada Wanita Usia Subur - Eliyana Eliyana; Sunarsih Sunarsih; Rosmiyati Rosmiyati; Ledy Octaviani Iqmy (Universitas Malahayati Lampung, 2025)
ABSTRACT Dysmenorrhea is a menstrual disorder characterized by pain or cramps in the abdomen. The pain is not only felt in the lower abdomen but can also be experienced in other areas such as the suprapubic region, lower back, thighs, and sides of the abdomen. One way to alleviate dysmenorrhea pain is by consuming guava leaves. The aim of this study is to determine the effectiveness of guava leaves in reducing menstrual pain (dysmenorrhea) in women of reproductive age in Mujimulyo Hamlet, Muara Putih Village, Natar District, South Lampung Regency in 2023.This study is quantitative research with a pre-experimental design using a one-group pretest and posttest approach. The population in this study consisted of women of reproductive age who experienced menstrual pain at BPM Eliyana based on medical records from November 2022 to February 2023, totaling 32 individuals, with a saturated sampling technique where all members of the population were included as the sample. The data were analyzed using the Wilcoxon test. The average dysmenorrhea pain score before administering guava leaves was 7.84, and after administering guava leaves, the average score dropped to 2.46. There is a significant effect of guava leaves in reducing menstrual pain or dysmenorrhea in women of reproductive age, with a p-value of 0.000 0.05. It is recommended that women of reproductive age consume guava leaves as an effort to reduce menstrual pain. Keywords: Dysmenorrhea, Guava Leaves, Women of Childbearing Age ABSTRAK Disminore adalah gangguan saat menstruasi berupa nyeri atau kram perut. Nyeri bukan hanya dirasakan diperut bagian bawah, tetapi juga dilokasi lain seperti suprapubik, punggung bagian bawah, paha, sisi abdomen. Upaya yang dapat mengatasi nyeri disminore yaitu dengan mengkonsumsi daun jambu biji. Tujuan penelitian ini untuk mengetahui pengaruh efektifitas daun jambu biji terhadap nyeri haid (dysminorrhea) pada wanita usia subur di Dusun Mujimulyo Desa Muara Putih Kecamatan Natar Kabupaten Lampung Selatan Tahun 2023. Jenis penelitian ini adalah kuantitatif dengan rancangan pre experiment dengan pendekatan one group pretest and posttest design. Populasi dalam penelitian ini adalah wanita usia subur yang mengalami nyeri haid di BPM Eliyana berdasarkan data rekam medik pada bulan November 2022-Februari 2023 berjumlah 32 orang dengan menggunakan teknik sampling jenuh dimana semua anggota populasi dijadikan sampel. Analisis data yang digunakan uji wilcoxon. Didapatkan nilai rata-rata nyeri disminore sebelum diberikan daun jambu biji adalah 7,84 dan sesudah diberikan daun jambu biji didapatkan rata-rata 2,46. Ada pengaruh pemberian daun jambu biji terhadap nyeri haid atau disminore pada wanita usia subur dengan nilai p value 0,000 0,05. Diharapkan wanita usia subur dapat mengkonsumsi daun jambu biji sebagai upayamengurangi nyeri haid. Kata Kunci: Desminore, Daun Jambu Biji, Wanita Usia Subur